Examining L1 ability in a Finnish secondary education context: A comparison of CLIL and non-CLIL students’ oral production - Launonen, Peter (John Benjamins Publishing Company, 2026)
This article examines the relationship between L1 ability and CLIL in a lower secondary education context in Finland. In the study, 31 participants responded to a verbal fluency task, a picture-naming task and a survey comprising L1 self-evaluation questions. The results were analysed quantitatively in light of additional variables such as socioeconomic status and L1 grades. The CLIL students outperformed the non-CLIL students in the verbal fluency task, whereas the results of the picture-naming task were not suggestive of group-level differences. Additionally, the CLIL students' picture-naming task results were less reflective of within-group differences than those of the non-CLIL students. This study sheds light on the relationship between CLIL and L1 ability, while highlighting the possible role of CLIL in mitigating the impact of individual differences on L1 ability.